Estudo de viabilidade de implantação de travessia de pedestres em diagonal. Estudo de caso: cruzamento da Av. Presidente Vargas com a Rua Carlos Gomes em Belém-PA - ALMEIDA, Marivana Figueredo de (2021)
The National Urban Mobility Policy, Federal Law 12587/2012, establishes as one of its guidelines the priority of non-motorized transport over motorized transport. It turns out that this priority is not always observed in the daily life of Brazilian cities. Therefore, the objective of this work is to investigate the feasibility of implementing an X-shaped pedestrian crossing at the intersection of Avenida Presidente Vargas and Rua Carlos Gomes, in the center of Belém, a measure that would favor the safety and fluidity of the traffic of pedestrians in the city. local. To this end, counts of pedestrian and vehicle flows at the intersection were carried out, in addition to measuring the dimensions of the roads. The dimensioning of the traffic light programming was done according to the recommendations of the DENATRAN Manual and the crossing signaling in X was guided by the recommendations of CET-SP. The main results were: Verification that the current traffic light was not dimensioned according to the DENATRAN Manual, as it does not have the general red. High flow of people, on the order of around 800 pedestrians/hour in a crossing, which justifies the implementation of pedestrian traffic lights. Increased cycle time, from 105 s to 116 s, 7% increase in time allowed for pedestrians, 20.35% reduction in P. Vargas' green time and 3% for C. Gomes. For scenario 1 analyzed, it was found that the reduction of crossing lanes has a small impact on the time lost for pedestrian crossing and for scenario 2, a schedule was made that prioritizes the pedestrian and is achievable, with 21.9 % reduction in time to green for Presidente Vargas and 4.8% reduction in time to green for Carlos Gomes. Finally, it is recommended to implement the crossing in X at the confluence of Presidente Vargas x Carlos Gomes, duly supported by traffic education actions.